Combinations of mild chemical and bacterial pretreatment for improving enzymatic saccharification of corn stover - Guoqing Liu; Dongjing Han; Shaohua Yang (Biotechnology & Biotechnological Equipment, 2022)
AbstractBiological pretreatment of lignocellulosic biomass plays an important role for the enzymatic hydrolysis. In this study, a nitrogen-fixing and lignin-degrading strain of bacteria was isolated from an abandoned termite colony. Then, it was identified and named as R. ornithinolytica RS-1. To improve the degradation and enzymatic saccharification in corn stover, we used pretreatment with strain RS-1 to deplete the lignin, combined with a 2.5% mild NaOH pretreatment to further deplete the hemicellulose. After only seven days, lignin was degraded by the bacteria RS-1 with a 19% decrease, while the relative content of cellulose increased with 21%. Furthermore, the corn stover cellulose conversion was up to 48.58% by a two-stage process with 2.5% NaOH pretreatment. Meanwhile, significant lignin and hemicellulose removal were observed. Manganese peroxidase activity was highest on Day 3 with the value 181.0256 U/L and lignin peroxidase activity was highest on Day 5 with the value 37.473 U/L, respectively. Scanning electron microscopy (SEM), Fourier transform infrared spectroscopy (FT-IR) and X-ray diffraction (XRD) analyses showed significant chemical structural changes after the combined pretreatment. Therefore, strain RS-1 provided an efficient strategy to enhance the enzymatic hydrolysis efficiency by pretreatment of corn stover.